Adventures in peptides and science with students! the joys of research. Issue 2 (24th April 2013) - Hruby, Victor J.
<x xml:space="preserve">Abstract</x> Working with students at the undergraduate, graduate and postdoctoral levels has brought me great joy and satisfaction. Each student is a unique human being, so each provides an important opportunity for learning, creativity and accomplishment in research and scholarship. In this reflection, several examples of this scientific process are discussed in the context of solving scientific problems which led to novel and critical scientific insights. © 2012 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 100: 127–131, 2013.